Workload Management for Grid Environment with the Restriction on the Waiting Time - Sahakyan, Vladimir; Petrosyan, Sergey (Mathematical Problems of Computer Science, 2021)
Resource management and job scheduling in multiprocessor computing system and Grid environment are challenging problems. Although significant results were achieved in the past, there are some problems that still exist, and need to be completely solved. More restrictions in job will make queue management run efficiently. One of the main parameters in the job scheduling is a waiting time. Waiting time is the time period, that job is ready to wait until it runs. In this article one approach to organize workload management is considered, it gives an overall solution for problem, and may be upgraded to support nonhomogeneous systems or adding some new fetchers. The article offers two parametric models of queue service discipline FIFO with optimizations and restriction on waiting time. The models will be compared and underlined within the main usage of two models.